Epidural Labor Analgesia Childbirth Without Pain - Capogna, Giorgio (Springer International Publishing : Imprint: Springer, 2015)
This book offers an in-depth examination of labor pain and analgesia with the aim of promoting natural childbirth without pain. All aspects of the subject are covered, including the latest techniques of delivering labor analgesia. Importantly, emphasis is placed on a holistic approach, detailed attention being paid to the humanization of childbirth and behavioral aspects in addition to evidence-based medicine. Potential future developments are also addressed, with discussion of opportunities that have yet to be realized. In order to ensure that the text is easily readable for trainees as well as established practitioners, chapters have been restricted to a manageable length and information is presented clearly and succinctly. Step-by-step tutorials and boxes highlighting practical points are used to clarify technical aspects. The authors include both well-established experts and young emerging professionals from various European countries, ensuring an intercultural perspective.